(untitled) (Research, Society and Development, 2021)
Introduction: Inherent in most procedures performed in the Neonatal Intensive Care Unit, pain is a phenomenon that needs to be correctly and early evaluated and treated so that it does not harm the baby’s development in the long term. Its non-pharmacological therapy does not block the transmission of nociceptive stimuli to the thalamus and activates descending inhibitory pathways, being an important and diverse ally in pain control. Methodology: This is an Integrative Literature Review carried out with an initial search of the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and Medical Literature Analysis and Retrieval System databases (Medline). The search term “Intensive Care Units, Neonatal AND Pain management” was used. Publications from 2017 to 2021 were included and review articles, meta-analyses and case reports were excluded. There were no duplications. Articles whose title or abstract corroborated the purpose of this review were also excluded. The 18 articles filtered by the exclusion criteria were organized and, after reading all of their content, 14 articles that make up the results of this review were retrieved. Results and Discussion: All retrieved articles are randomizations and most of them were published in 2020. It was observed that heel puncture is a painful procedure and evaluated in most clinical trials, including the application of the Premature Infant Pain Profile scale (PIPP), for studies with preterms. Furthermore, it was found that 24% oral sucrose was the intervention most compared to others and that it was inferior or comparable to the kangaroo method and the intake of breast milk for pain control in neonates hospitalized in the ICU. Conclusion: this review pointed out the clinical effectiveness of interventions of different natures evidenced in the rescued studies. Smell, hearing, taste and touch have been potential fields of intervention for analgesic control or pain distraction in neonates undergoing routine painful procedures. It is noteworthy that the kangaroo method, the intake of breast milk and its odor, as well as the sound of the maternal heartbeat have shown positive, safe and reproducible results, even in comparison with the use of oral sucrose at 24%. It is noteworthy that new clinical trials and meta-analyses are essential to strengthen the conclusions of this study.